Analysis of Health Service Utilization in Post-Screening Dental and Oral Examination Follow-Up for Elementary School Children - Lysa Sabrina Sitepu; Ida Yustina; Gema Nazri Yanti (Journal La Medihealtico, 2025)
The utilization of health services after dental and oral health screening among elementary school children is an issue that requires serious attention, particularly in relation to efforts for the early prevention and control of dental diseases. This study aimed to analyze the factors influencing the utilization of health services for follow-up examinations after dental and oral health screening among elementary school children in Karo District. The study employed an analytic survey with a cross-sectional design. The sample size was determined using the Isaac and Michael table, resulting in 232 mothers whose children were diagnosed with dental caries, selected through multistage sampling. Data were collected using a validated and reliable questionnaire and analyzed with multiple logistic regression. The findings showed that the utilization of health services for follow-up examinations after dental and oral health screening among elementary school children in Karo District was 13.4%, far below the target (100%). The analysis indicated that predisposing, enabling, and need factors had a significant influence on the utilization of health services for follow-up examinations after screening, with a p-value < 0.005 and Exp (β) of 1.086. These factors were shown to significantly affect health service utilization. Efforts are needed to improve oral health education, empower families, and optimize the role of community health centers and schools in supporting the utilization of health services after screening.